2009
DOI: 10.1111/j.1365-2613.2008.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruziand myoid cells from seminiferous tubules: interaction and relation with fibrous components of extracellular matrix in experimental Chagas’ disease

Abstract: The main transmission route of Trypanosoma cruzi is by triatomine bugs. However, T. cruzi is also transmitted through blood transfusion, organ transplantation, ingestion of contaminated food or fluids, or is congenital. Sexual transmission, although suggested since the discovery of Chagas' disease, has remained unproven. Sexual transmission would require T. cruzi to be located at the testes and ovaries. Here we investigated whether T. cruzi is present in the gonads of mice infected with 10(4) T. cruzi trypomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…In the T. cruzi-infected rodent Calomys callosus histopathological lesions in the heart and skeletal muscles have been associated with high levels of the cytokines TNF-␣, IFN-␥, and TGF-␤ (254). In this context, the presence of amastigote nests and alterations in the extracellular matrix have been reported (57).…”
Section: Autoimmunitymentioning
confidence: 99%
“…In the T. cruzi-infected rodent Calomys callosus histopathological lesions in the heart and skeletal muscles have been associated with high levels of the cytokines TNF-␣, IFN-␥, and TGF-␤ (254). In this context, the presence of amastigote nests and alterations in the extracellular matrix have been reported (57).…”
Section: Autoimmunitymentioning
confidence: 99%
“…[7][8][9][10]12,15,16,[18][19][20][21][22][23][24] However, information is scarce and controversial regarding T. cruzi infections (that affect the reproductive system) and the direct transmission of such infections through coitus. 11,13,14 The latest report by Carvalho and others 17 showed that T. cruzi can colonize different cells, including myod cells, and suggested the possibility of parasite migration to the seminal fluid in case of a rupture of these cells. Therefore, the CD could potentially be transmitted through sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…These researchers have also reported the shedding of parasites in the semen accompanied by several reproductive disorders, such as low semen quality, reduced libido, testicular degeneration, impaired spermatogenesis, and alterations in the extracellular matrix of the lamina propria of the seminiferous tubules. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The presence of trypanosomatids in the semen of infected dogs indicates the possibility of venereal transmission of CD. Therefore, the use of chagasic dogs as sires should be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, experimental infection has further shed light on the disseminative capability of this organism during the acute phase of the disease into the male and female genital organs. In a mouse model of infection, T. cruzi was detected in the preputial glands and skin, penis, testicular albuginea, epididymis, vas deferens, seminal vesicles, prostate, and urethral glands [322,323]. In females, T. cruzi invades cells of the vagina, uterus, oviduct, ovary, and clitoris [313,315].…”
Section: Genital Organs: Semen/vulvular Secretionmentioning
confidence: 99%